A Smart Disaster Governance Model for Local Governments: Integrating the Internet of Things, Big Data, and Public Participation in Disaster Management - Lalu Ahmad Murdhani (Yayasan Hisnul Muslim Lombok, 2026)
This study examines the development of a smart disaster governance model for local governments in Indonesia by integrating the Internet of Things, big data, and public participation in disaster management. The study is based on the argument that disaster governance can no longer rely solely on conventional administrative procedures, sectoral reporting, and reactive emergency response. Local governments need a governance framework that enables real-time risk monitoring, interoperable disaster data, data-driven decision-making, cross-sectoral coordination, and citizen engagement. Using a qualitative case study approach, this research analyzes institutional readiness, digital disaster infrastructure, IoT-based monitoring, big data utilization, public reporting mechanisms, and participatory coordination in disaster-prone local government contexts. Data were collected through in-depth interviews, field observations, and document analysis involving regional disaster management agencies, communication and informatics offices, planning agencies, public works offices, health and social affairs offices, command center operators, disaster volunteers, community leaders, and residents in disaster-prone areas. The findings show that digital tools have begun to support disaster management, but their effectiveness remains limited by fragmented data, weak interoperability, unclear institutional responsibilities, and insufficient integration of citizen-generated information. This study proposes a smart disaster governance model consisting of six components: real-time risk monitoring, integrated disaster data platform, big data-based decision support, participatory public reporting, cross-sectoral command coordination, and accountability-based evaluation. The novelty of this study lies in integrating technological intelligence, institutional intelligence, and social intelligence into one local government disaster governance framework.